Geographical distribution of the vector species Trypanosoma cruzi for Chagas disease in Ecuador: A narrative review - Glenda Velasquez; Joel David Carrera Gonzalez; Angie Fiorella Suarez Ubilla; Diana Berzina (Population Medicine)
Chagas disease is a complex clinical entity caused by a protozoan parasite, Trypanosoma cruzi, transmitted by the bite of infected triatomines. The objective of this study was to establish the distribution of vector species of T. cruzi according to all the geopolitical regions of Ecuador. This narrative review was conducted from December 2022 to July 2023 by searching the following databases: PubMed, Elsevier, Google Scholar, Scielo, Latindex, and Dialnet. Also, websites of international and national health organizations: WHO and PAHO, Epidemiological Gazette of Ecuador, SIVE-ALERTA, Ministry of Public Health of Ecuador, and national repositories of theses generated by Ecuadorian universities. In the Coastal region, T. dimidiata was found as the predominant vector (83%), followed by Panstrongylus howardi, P. chinai and P. geniculatus, all with the same percentage of circulation (33%) and Rhodnius ecuadoriensis (17%). In the Andean region, the most important species was R. ecuadoriensis in the Province of Loja (59%). The province of Orellana (Amazon region) had the highest value of R=0.471 and greater species diversity (P. geniculatus, P. lignarius, R. robustus, R. pictipes, R. pallences, R. barreti, E. cuspidatus, E. mucronatu). Currently, the circulation of 4 genera and 17 species of triatomines is reported in Ecuador. It is necessary to expand the collection sites in different regions to update the geographical distribution of triatomine species circulating in Ecuadorian territory.